Corporate social responsibility of pharmaceutical industry in Korea - Green Bae; Jeong-Hoon Ahn; Kyung-Min Lim; SeungJin Bae (Frontiers in Pharmacology, 2022)
Background: Global pharmaceutical companies in Korea argue that the development of innovative drugs should be recognized as a social contribution, yet it has been countered by various stakeholders. The need to distinguish between philanthropic activities and Corporate Social Responsibility (CSR) of pharmaceutical companies and reaching consensus in the Korean context has been raised. We sought to evaluate the CSR status of Korean pharmaceutical companies and collect the stakeholders’ opinions to define philanthropic activities and CSR related to pharmaceutical companies in Korea.Methods: We conducted a literature review on the definition of CSR of pharmaceutical companies, and the CSR activities of the domestic pharmaceutical companies were compared with those of global pharmaceutical companies operating in Korea. The opinions of stakeholder groups (patient advocate groups, consumer organizations, and domestic/global pharmaceutical companies) were collected using focus group interviews (FGI) and written surveys.Results: Literature review suggested that CSR is categorized as “must do” (economic and legal responsibilities), “ought to do” (ethical responsibilities), and “can do” (philanthropic responsibilities), whereas contributions beyond the economic, legal, or ethical responsibilities can be defined as “can do” (philanthropic responsibilities). Domestic pharmaceutical companies simply adopted systems for ethical and ESG (Environmental, Social, and Governance) management, which are at the “ought to do” level (ethical responsibility), whereas the headquarters of these global pharmaceutical companies established the CSR team and systematically reported on the CSR activity, including ESG management reports, which is at the “ought to do” level and further moving to the “can do” level, but the Korean branch rarely has CSR teams, and the CSR activities in Korea were also insufficient. At the FGI, the global pharmaceutical companies argued that CSR activities, such as innovative drug development, should be recognized as similar to philanthropic activities, yet stakeholders besides them suggested that those activities are “can do” rather than being philanthropic.Discussion: We found that the pharmaceutical companies in Korea are attempting to achieve the “ought to do” level (ethical responsibilities) while complying with the “must do” level (legal and economic responsibilities) yet not philanthropic activities. A social consensus regarding the philanthropic responsibilities of pharmaceutical companies in Korea was not reached.